Functional and transcriptional analysis of chromosomal encoded hipBAXn2 type II toxin-antitoxin (TA) module from Xenorhabdus nematophila. (January 2022) - Yadav, Mohit; Rathore, Jitendra Singh
Abstract: Xenorhabdus nematophila is an entomopathogenic bacterium that synthesizes numerous toxins and kills its larval insect host. Apart from such toxins, its genome also has a plethora of toxin-antitoxin (TA) systems. The role of TA systems in bacterial physiology is debatable; however, they are associated with maintaining bacterial genomic stability and their survival under adverse environmental conditions. Here, we explored the functionality and transcriptional regulation of the type II hipBA Xn2 TA system. This TA system was identified in the genome of X. nematophila ATCC 19061, which consists of the hipA Xn2 toxin gene encoding 278 amino acid residues and hipB Xn2 encoding antitoxin of 135 amino acid residues. We showed that overexpression of HipA Xn2 toxin reduced the growth of Escherichia coli cells in a bacteriostatic manner, and amino-acids G8, H164, N167, and S169 were key residues for this growth reduction. Promoter activity and expression profiling of the hipBA Xn2 TA system was showed that transcription was induced in both E. coli as well as X. nematophila upon exposure to different stress conditions. Further, we have exhibited the binding features of HipA Xn2 toxin and HipB Xn2 antitoxin to their promoter. This study provides evidence for the presence of a functional and well-regulated hipBA Xn2 TA system in X. nematophila . Graphical abstract: Image 1 Highlights: Identification of the hipBA Xn2 TA homolog in the genome of X. nematophila . HipA Xn2 homologs belongs to serine/threonine kinases. HipB Xn2 homologs belongs to transcriptional regulators. hipBA Xn2 TA homolog is an authentic type II TA system.